2018
DOI: 10.35248/2593-9793.18.3.112
|View full text |Cite
|
Sign up to set email alerts
|

In-depth Analysis of Mortality in Relation to Malnutrition in Children Under-five of Age in the Eastern Mediterranean Region

Abstract: Background:The Eastern Mediterranean region (EMR) countries are facing many challenges that influence the nutritional status of children under-five years of age (CU5) and increase early mortality rates (MRs). Few studies have considered using global data to analyze the protective effect of breastfeeding on reducing MRs in the EMR.Aim: To analyze regional mortality rates in relation to socio-demographic, nutritional indices and early feeding practices in CU5 in the EMR countries.Methods: Data from the WHO globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Low prevalence of exclusive breastfeeding in the Arab world is concerning; some countries in the Arab world approach the global average but prevalence is much lower in others including in Somalia (5.3%) and Tunisia (8.1%) (Al-Jawaldeh et al, 2018 ; United Nations Office of the High Commissioner for Human Rights, 2016 ). A comprehensive analysis reported that suboptimal BF was identified as a leading child health risk factor in several Arab States including Algeria, Egypt, Iraq, Libya and Morocco (Roberts et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low prevalence of exclusive breastfeeding in the Arab world is concerning; some countries in the Arab world approach the global average but prevalence is much lower in others including in Somalia (5.3%) and Tunisia (8.1%) (Al-Jawaldeh et al, 2018 ; United Nations Office of the High Commissioner for Human Rights, 2016 ). A comprehensive analysis reported that suboptimal BF was identified as a leading child health risk factor in several Arab States including Algeria, Egypt, Iraq, Libya and Morocco (Roberts et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 Nevertheless, the decline in early initiation (within one hour of birth)—87.1% and 82.0%—and the current low rate of EBF for the first six months (23.2%) are of concern not only in Oman but also in the region as a whole. 3 , 5 , 6 …”
mentioning
confidence: 99%
“…3 Nevertheless, the decline in early initiation (within one hour of birth)-87.1% and 82.0%-and the current low rate of EBF for the first six months (23.2%) are of concern not only in Oman but also in the region as a whole. 3,5,6 A wide range of factors, including social and cultural attitudes, marketing of infant formula, health systems and workplace, community settings and individual attitudes, affect whether or not women initiate early breastfeeding and maintain exclusive and continued breastfeeding for up to two years. 2 Barrier analysis, based on the Health Belief Model and the Theory of Reasoned Action, has identified 12 determinants of behaviour: perceived selfefficacy, perceived social norms, perceived positive consequences, perceived negative consequences, perceived action efficacy, access, perceived susceptibility/risk, perceived severity, cues for action, policy, culture and perceived divine will.…”
mentioning
confidence: 99%